Characterization of a Tembusu Virus Isolated from Naturally Infected House Sparrows (Passer domesticus) in Northern China. Issue 2 (20th April 2012) - Tang, Y.; Diao, Y.; Yu, C.; Gao, X.; Ju, X.; Xue, C.; Liu, X.; Ge, P.; Qu, J.; Zhang, D.
Summary The house sparrow (Passer domesticus) is one of the most widely distributed wild birds in China. Tembusu virus (TMUV) strain, TMUV‐SDHS, was isolated from house sparrows living around the poultry farms in Shandong Province, Northern China. Genetic analysis of E and NS5 genes showed that it had a close relationship with that of the YY5 strain, which can cause severe egg drop in ducks. Pathogenicity studies showed that the virus is highly virulent when experimentally inoculated into the ducks. These findings show that house sparrows carrying the Tembusu virus may play an important role in transmitting the virus among other species.